Etika dan Tantangan Penggunaan Kecerdasan Buatan dalam Kedokteran Gigi - Fauziah, Yessy Andriani; Alhadad, Husin; Prawira Utama, Yudhistira (Magister Ilmu Hukum - Universitas Hang Tuah, 2024)
The integration of artificial intelligence (AI) in dentistry has brought significant advancements in diagnosis, treatment planning, and improving healthcare services. However, the rapid adoption of AI raises ethical challenges, such as data privacy, clinical decision-making processes, and the potential reduction in human interaction. This study aims to analyze the ethical implications and legal challenges associated with the use of AI in dental practice. The method used is normative legal research based on literature, focusing on relevant regulations and legal concepts. This review highlights key issues such as informed consent, transparency in decision-making, and the role of dentists as overseers of AI technology. Additionally, the urgent need for a legal framework ensuring the ethical use of AI is discussed, to ensure that this technology enhances care without compromising standards. While AI has the potential to improve diagnostic accuracy and operational efficiency, dentists must ensure a balance between innovation and ethical obligations, emphasizing the importance of sustained ethical guidelines.